Seafloor Displacement After the 2011 Tohoku‐oki Earthquake in the Northern Japan Trench Examined by Repeated Bathymetric Surveys. Issue 23 (14th December 2017) - Fujiwara, Toshiya; dos Santos Ferreira, Christian; Bachmann, Anna Katharina; Strasser, Michael; Wefer, Gerold; Sun, Tianhaozhe; Kanamatsu, Toshiya; Kodaira, Shuichi
Abstract: We conducted multibeam bathymetric surveys crossing the northern Japan Trench offshore Sanriku and examined seafloor displacement by means of the difference in bathymetry before and after the 11 March 2011 Tohoku‐oki earthquake. The seafloor displacements were less than several meters in vertical displacement and less than 20 m in trench‐normal horizontal displacement; consequently, lower amplitude seafloor displacements were evaluated. Comparatively, the landward lower slope near the trench was uplifted, the middle slope was subsided, and the midslope terrace was depressed after the earthquake. Therefore, localized very large fault slip or very large submarine landslide is unlikely. Instead, smaller uplift of the lower slope near the trench extending broader along the trench seems to be plausible explanation for the devastating tsunami source in the northern Japan Trench area. Key Points: Seafloor displacement in the northern Japan Trench was examined by difference in bathymetry before and after the 2011 Tohoku‐oki earthquake Large horizontal/vertical seafloor displacements were not found; thus, there is no evidence of localized large thrust fault slip or submarine landslide The outermost landward lower slope was uplifted, and the middle slope and the midslope terrace were subsided with amplitudes of several meters